PENENTUAN JENIS DRAFT TUBE BERDASARKAN NILAI HEAD RECOVERY DAN KINERJA TURBIN HYDROCOIL MENGGUNAKAN METODE COMPUTATIONAL FLUID DYNAMICS - Hidayat, Fahmi; Luthfie, Alief Avicenna; Biantoro, Agung Wahyudi (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2023)
A Microhydro Power Plant (MHP) with hydrocoil turbine in Sukajaya Lembang Village, Bandung, West Java, has been successfully designed. However, the velocity of the water flow after exiting the hydrocoil turbine is still relatively high, so there is still a lot of wasted flow energy before it can be converted. Like other reaction turbines, the hydrocoil turbine requires a draft tube in order to maximize its energy conversion process. Thus, the purpose of this research is to determine the type of draft tube based on the head recovery value and performance of the hydrocoil turbine for the MHP system. This determination process involves 3 stages: 1) evaluation of the performance of the hydrocoil turbine that has been installed with three types of draft tubes, namely conical straight, curved elbow, and simple elbow, by Computational Fluid Dynamics (CFD), 2) calculation of the head recovery of the three types of draft tubes, and 3) determination of the best draft tube based on the head recovery value and performance of the hydrocoil turbine. In stage one, the type of analysis used is steady state with the SST k-ω turbulence model, to capture turbulence in the penstock pipe and near the turbine blades. As the results, the highest hydrocoil turbine efficiency with all three types of draft tubes installed, is at a rotational speed of N=1100 rpm. The highest efficiency for the hydrocoil turbine with conical straight, curved elbow, and simple elbow draft tubes are 90.48%, 90.18%, and 91.26%, respectively. Meanwhile, the head recovery at rotational speed N=1100 rpm for conical straight, curved elbow, and simple elbow draft tubes are 1.627 m, 1.866 m, and 4.097 m, respectively. Thus, the simple elbow draft tube is the best to use in this MHP system because it has the highest head recovery and efficiency values.